Work-related self-reported musculoskeletal disorders in hypermarket cashiers: a study in south of Portugal - Minghelli, Beatriz; Ettro, Nelma; Simão, Jéssica; Maurício, Karina (La Medicina del Lavoro, 2019)
Background: Work-related musculoskeletal disorders are a group of painful disorders which arise from work situations with continuous repetitive movements, carried out with speed and without time for recovery. In the performance of their job tasks, supermarket cashiers are exposed to this type of ergonomic stress. Objectives: This study aimed to determine the incidence of self-reported injuries in Portuguese hypermarket cashiers and to identify the related factors. Methods: The sample included 176 hypermarket cashiers, aged between 18 and 65 years (39.57±11.11), 167 (94.9%) of them women. Symptoms and exposure of interest have been collected through an interview-based questionnaire. The presence of carpal tunnel syndrome was assessed by Phalen’s test. Results: One hundred and seventeen (66.5%) cashiers reported an injury during employment, 100 (56.8%) of them reporting an injury in the previous 6 months. A total of 166 injuries were reported, corresponding to 1.14 injuries per 1,000 hours of work. The most common injuries were non-specific pain (30.4%), located in the shoulder (23.2%), cervical (22%) and lumbar spine (22%). Part-time workers showed a 2.25 times greater risk of injury (95% CI: 1.17-4.32; p=0.015) than full-time workers. Cashiers with more than 6 years of employment length had a 3.59 times higher risk of injury (95% CI: 1.84-6.99; p≤0.001) than those who had been working for a shorter period. Conclusions: Our data showed a high rate of reported injuries among hypermarket cashiers, especially among part-time workers and those with the highest length of employment.